L’imparfait et la ponctualité - Lim, Jung-Hae (Neophilologica, 2008)
The article discusses the role of French tense Imparfait and its interpretation in the Korean language. The basic notions to recognize the value of the verb are : the semantic value of the topic, the combination with different classes of adverbs and the value of grammar tenses. On the basis of several examples, the author of this article shows that the French past tense Imparfait can be interpreted in several ways : as a punctual tense or as a durative tense.